(3ebGdI aj NUH GdHOfs - (3LGdjfhSs
(3ChdgG (B:s
(3bGd LGdjfhS bO LQJ YGOJfG eYTQ GdjhfGfjf jUQa GSe NUH GdHOf Ydi cd TF s
(3BNQgG (B:s
(3hCeG bhdg hGfaYGd GdYQhb ajYfi Hg GeJdGhgG GdeaQW MJi dGjchf dgG faS JJQhL Hg cedJ GdebGdI ai NUH GdHOf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdSGOSs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs